Specifics of Formation and Development of Students’ Independence in the Digital Educational Environment - Dmitriy Kozhevnikov; Maria Pobedonostseva; Maryana Farnieva (ARPHA proceedings, 2020)
The relevance of the study of the problem of formation and development of students’ independence is due to the active formation of the digital educational environment in the conditions of unknown consequences and risks of students’ adaptation to the conditions of life in the digital world.The purpose of the study is to identify the risks of students’ adaptation to the conditions of life in the digital world in the context of formation and development of their independence in the digital educational environment, as well as to search for possible solutions to these problems.The study was based on the analysis of changes that have occurred in the communication sphere and educational environment due to the widespread use of electronic means of communication and information technologies. The solution is being searched when students activate the reserves of various models of information perception.The paper discusses the trends and consequences of the students’ constant use of information support of the Internet, which ambiguously influences the development of their creative abilities. The study also revealed changes in the content and the transformation of teachers and students’ ideas about self-educating activities. It states the problem of formation and development of students’ autonomy in a digital learning environment.Aiming at solving the identified problem, the materials presented in the paper allow us to offer not only interactive opportunities and a variability of tasks aimed at the subject-oriented motivation of students, but also the use of material sign-symbolic models that require individual manipulative activity. The authors developed the method of using contour objects and models, the scale and design of which provide for various operations with them using fingers, which helps to concentrate students’ attention on their actions with objects. They also initiate individual creative activity and independence of actions.Fragments of training programs were prepared; experimental courses were conducted in the format of additional education in groups of students using specialized sets for constructing sign and symbolic models in the form of contour shapes.